The unicity of best approximation in a space of compact operators - Kowynia, Joanna (MATHEMATICA SCANDINAVICA, 2011)
Chebyshev subspaces of K(c_0,c_0) are studied. A k-dimensional non-interpolating Chebyshev subspace is constructed. The unicity of best approximation in non-Chebyshev subspaces is considered.